190 °C High-Temperature Operation of 905-nm VCSELs With High Performance - Xun, Meng; Pan, Guanzhong; Zhao, Zhuang Zhuang; Sun, Yun; Zhou, Jingtao; Wu, Dexin (IEEE transactions on electron devices, 2021)
Greater than 190 °C continuous wave (CW) lasing is achieved from 905 nm high-efficiency vertical cavity surface-emitting lasers (VCSELs). The maximum power conversion efficiency (PCE) of 46.3% for {4}~μ \text{m} VCSELs was demonstrated under the ambient temperature of 30 °C. The maximum PCE decreases only 10% of its value from 30 °C to 90 °C, showing stable high-temperature characteristics. The thermal resistances and active region temperatures of the device versus ambient temperature are determined experimentally. Besides, size-dependent thermal characteristics are also analyzed by characterizing the spectral and spatial properties of devices with various apertures. It is found that the higher the ambient temperature is, the less the number of high-order modes is, and single fundamental mode operation can be realized in {4}~μ \text{m} VCSELs even at a relatively high temperature of 190 °C. The design and characterization of these high-temperature VCSEL devices might present the basis for future laser radar application.